Tinjauan Praktek Akad Ijarah Menurut Hukum Islam: Studi Kasus pada UMKM Kios di Kec. Medan Helvetia - Shavira Aprilia; Rasta Kurniawati Br. Pinem (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Leasing (ijarah) is a form of muamalah action that is often carried out by humans to fulfil their needs. These needs can be in the form of the benefits of goods or services that are not owned, such as renting out kiosks for MSME business actors in Medan Helvetia Sub-District. However, in some cases, kiosk tenants are often not responsible for the leased kiosk building, such as building damage that arises during the lease period and arrears in water and electricity costs. The purpose of this study is to explain how the practice of ijarah contracts contained in kiosk MSMEs in Medan Helvetia sub-district and explain the practice of ijarah contracts contained in kiosk MSMEs in Medan Helvetia sub-district according to Islamic law. This research uses a type of field research with a descriptive qualitative approach. The data sources used are primary data sources and secondary data sources. Data collection is done by observation, interviews, documentation. Data analysis techniques using qualitative descriptive data analysis techniques. Based on the results of this research, the benefits of objects in the practice of ijarah contracts for MSME kiosks in Medan Helvetia sub-district are permissible in Shara'. When viewed from the validity of the contract, the practice of ijarah contracts for MSME kiosks in Medan Helvetia Sub-District is not in accordance with Islamic law because the conditions for the validity of the ijarah contract have not been fulfilled, which is due to violations committed by the tenant against the object of the lease in the form of damage to the building that appears.